2019
DOI: 10.5114/hpr.2019.85952
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency as a predictor of flexibility in coping with stress of cardiac patients

Abstract: health psychology report • volume 7(3), 9 original article background Since cardiovascular diseases remain the main cause of premature mortality in men and women in Poland, it is reasonable to look for factors that protect against these conditions. Psychological resiliency is one of such properties that support adaptation in difficult situations and conducive to adaptation to the disease. The aim of the present study was to analyze the relationship between resiliency and flexibility in coping of cardiac pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Existing research has not provided much insight into the relationship between flexible coping and personal resources. People who were more resilient and hopeful proved to be more flexible in coping with stress (Basińska et al, 2017;Borzyszkowska & Basińska, 2018;Góralska & Basińska, 2019). Studies involving people with chronic diseases confirmed that those with a higher sense of coherence and stronger spirituality were more flexible (Basińska, 2015).…”
Section: Flexibility In Coping and Its Importance In Functioning Durimentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has not provided much insight into the relationship between flexible coping and personal resources. People who were more resilient and hopeful proved to be more flexible in coping with stress (Basińska et al, 2017;Borzyszkowska & Basińska, 2018;Góralska & Basińska, 2019). Studies involving people with chronic diseases confirmed that those with a higher sense of coherence and stronger spirituality were more flexible (Basińska, 2015).…”
Section: Flexibility In Coping and Its Importance In Functioning Durimentioning
confidence: 99%
“…An individual is prepared to look for an adequate coping method and use different psychological and behavioural coping strategies interchangeably. A high result in the Reflexivity subscale shows that the individual is able to reflect on the strategies applied for dealing with stress in the aspect of accepted values and also to accept the difficult situation in which he or she has found him or herself (Borzyszkowska & Basińska, 2018;Góralska & Basińska, 2019;Stępka-Tykwińska, Basińska, Sołtys, & Piórowska, 2019).…”
Section: Operationalisation Of Variablesmentioning
confidence: 99%
“…Resilient people are able to adapt their affective and physiological responses in order to meet the demands of changing environmental conditions [22], and this facility may also form the basis of coping better with somatic diseases. Ego-resiliency improves the person's ability to adapt to the situation after a heart transplant [23], other cardiovascular disease [24], chronic pain [25], or cancer [26]. Heart transplant recipients with higher levels of this variable are more likely to comply with medical recommendations, maintain a healthy and active lifestyle, cope better with negative emotions, and have more satisfying social relationships [23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Heart transplant recipients with higher levels of this variable are more likely to comply with medical recommendations, maintain a healthy and active lifestyle, cope better with negative emotions, and have more satisfying social relationships [23]. Cardiac patients with a higher level of ego-resiliency are characterized by greater flexibility in coping with stress [24]. Individuals with chronic pain and high ego-resiliency report greater positive emotions and exhibit lower day-to-day pain catastrophizing [25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies such as Kruczek et al (2020) and Muyan-Yılık and Demir (2020) have shown positive correlation and direct effects between these variables. However, some studies have established that they are different concepts at the theoretical and empirical levels, showing that cognitive flexibility is just a component of a larger concept known as coping flexibility, which refers to the ability to modify coping strategies according to the level of effectiveness when dealing with a stressful situation ( Cheng, 2014 ; Góralska & Basiska, 2019 ; Kato, 2012 ; Kruczek et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%